Perancangan Alun-Alun Mini Berbasis 3D untuk Penguatan UMKM dan Pariwisata Desa Curahmalang - Sholahudin, Muhammad; Dzikrillah, Farissa Agnia; Safarina, Sofia Gita; Arfaah, Saiful; Muliono, Muhamad (Universitas Pahlawan Tuanku Tambusai, 2026)
The village square is a multifunctional public space that can serve as a center for social interaction and a driver of the local economy. The design of a mini square in Curahmalang Village through 3D modeling aims to support social development, empower MSMEs, and enhance local tourism appeal. Research methods included field surveys, focus group discussions (FGDs), and conceptual design using Google SketchUp. The resulting 3D model design encompasses facilities such as a parking area, MSME area, playground, green open space (park), and aesthetically pleasing and functional gathering spaces. 3D modeling has proven to provide clear visualizations that serve as both a planning blueprint and a promotional tool for tourist attractions. A well-organized square is predicted to increase social interaction among the community and the income of local MSMEs. This activity demonstrates the novelty of applying 3D modeling specifically for designing a village square, integrated with MSME empowerment and local tourism strategies.